Antibiotic-Induced, Increased Conjugative Transfer Is Common to Diverse Naturally Occurring ESBL Plasmids in Escherichia coli - Liu, Gang; Bogaj, Karolina; Bortolaia, Valeria; Olsen, John Elmerdahl; Thomsen, Line Elnif (Frontiers in Microbiology, 2019)
Previously, we showed that cefotaxime (CTX) exposure increases conjugative transfer of a blaCTX-M-1 encoding IncI1 plasmid (IncI1/pST49/CTX-M-1) in Escherichia coli in a SOS-independent manner. This study aimed at investigating whether the observation was unique for that plasmid/strain/antibiotic combination or whether antibiotic-induced plasmid transfer (PT) is a general phenomenon among plasmids in E. coli. Whole genome sequences of 25 E. coli strains were analysed to identify different ESBL plasmids enabling selection of a diverse collection of plasmids. Conjugation experiments were performed following exposure of these strains to ½ MIC of CTX, ampicillin (AMP) or ciprofloxacin (CIP) before conjugation experiments. The frequency of PT was measured and compared to that of donors not exposed to antibiotics. RT-qPCR was used to measure mRNA levels of five plasmid transfer genes and two SOS response genes in donors exposed to antibiotics. The PT of eight strains (30.8% of strains tested) with IncI1/pST7/CTX-M-1, IncI1/pST49/CTX-M-1, IncI1/pST3/CTX-M-1, IncI1/pST293/CTX-M-1, IncI1/pST295/CTX-M-1, IncI1/pST16/CTX-M-55, and IncFII/CTX-M-14 (n=2) plasmids were significantly increased following antibiotic exposure. CTX increased PT in all of these eight strain/plasmid combinations, AMP and CIP increased the PT in six and three strains, respectively. RT-qPCR showed that plasmid transfer genes were up-regulated in the presence of the three antibiotics, whereas SOS-response genes were up-regulated only following CIP exposure. Our findings reveal that antibiotics can increase PT in E. coli strains with various ESBL plasmids. Thus, antibiotic-induced conjugative transfer of ESBL plasmids appears to be a common phenomenon in E. coli, having important implications for assessing the risks of antibiotic use.